2009
DOI: 10.1007/s10014-009-0256-x
|View full text |Cite
|
Sign up to set email alerts
|

Primary Ewing’s sarcoma of the orbit: case report

Abstract: A 22-year-old man presented with tenderness and swelling of the left lateral part of the orbit. Computed tomography revealed a left intraorbital mass measuring 3 cm x 3 cm involving the left lateral wall of the orbit and the greater wing of the left sphenoid bone. Magnetic resonance imaging revealed that the intraorbital mass was extraneuroaxial. During surgery, the tumor was seen to arise from the lateral wall of the orbit and infiltrate into the left temporal muscle. Following the surgery, the patient was ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 33 publications
0
10
0
1
Order By: Relevance
“…35 The poor prognostic factors for ESFTs are metastatic disease at presentation, large tumor 45 cm, older age, male gender, central tumor location including skull, clavicle, ribs, pelvis, vertebrae, and the upper extremities. 35,[36][37][38] Orbital ESFT is considered to be less aggressive than ESFT at other locations in the body, [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]39 as the survival has been more than 6 months in majority of the reported cases. Although extraorbital extension is frequently reported with primary orbital ESFTs, systemic metastases at presentation or during follow-up duration is rare as per the available literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 The poor prognostic factors for ESFTs are metastatic disease at presentation, large tumor 45 cm, older age, male gender, central tumor location including skull, clavicle, ribs, pelvis, vertebrae, and the upper extremities. 35,[36][37][38] Orbital ESFT is considered to be less aggressive than ESFT at other locations in the body, [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]39 as the survival has been more than 6 months in majority of the reported cases. Although extraorbital extension is frequently reported with primary orbital ESFTs, systemic metastases at presentation or during follow-up duration is rare as per the available literature.…”
Section: Discussionmentioning
confidence: 99%
“…3 Primary orbital ESFT is extremely rare with isolated case reports and small case series reported in literature. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Herein we discuss the demographic profile, clinical features, radiological features, treatment modalities, and outcomes of primary orbital ESFTs.…”
Section: Introductionmentioning
confidence: 99%
“…Necrosis, hemorrhage and adjacent organ invasion could be partially detected, while calcification was never seen. As to the imaging features of orbital ES, only Kano, et al and Naqvi, et al mentioned it in their case reports that focused on the clinicopathologic features of orbital ES [2-3] . The two irregular orbit ES masses in their case reports were located in the left lateral wall of the orbit, and the greater wing of the sphenoid bone was involved.…”
Section: Discussionmentioning
confidence: 99%
“…14,16 A review of 22 cases of primary orbital ES found 7 patients died within an average of 17.1 months and none survived for more than 5 years. 9 To date, approximately 25 cases of primary orbital ES have been reported; however, no reports comment on favorable treatment of recurrent disease. The technique described in this report requires the multidisciplinary efforts of ophthalmologists, radiation oncologists, pediatric oncologists, dentists, radiation physicists, radiologists, and nurses.…”
Section: Discussionmentioning
confidence: 99%
“…1214 Recurrent ES carries a poor prognosis 15 with no past reports of successful treatment of recurrent primary ES of the orbit, which often progresses rapidly and has a propensity to metastasize. 9,10,16,17 The authors report a case of primary extraskeletal ES of the orbit in a 6-year-old boy and successful treatment using a unique multimodal treatment approach. This case report is in compliance with the Health Information Portability and Accountability Act and followed the principles of the Declaration of Helsinki.…”
Section: Case Reportmentioning
confidence: 99%